Clinicopathological study on presentation, diagnosis and management of liver abscess in Bhopal region - Siroliya, Anshul; Damor, Mahendra; Songra, M. C. (International Surgery Journal, 2017)
Background: This prospective observational study is carried out to study cases of liver abscess and to determine demographic profile, spectrum of clinical presentations, aetiology, laboratory investigations. The objective of the study was to evaluate efficacy of Ultrasonographic (radiological) studies in determining the aetiology and in differentiating from other liver pathologies which may change the treatment outcome, bacteriological and serological characteristics, to study the influence of alcohol, diabetics and immunocompromised diseases (esp. HIV) leading to increased incidence of liver abscess and to evaluate efficacy, recurrence rate, complications, morbidity and mortality, duration of hospital stay associated with different management Strategies. Methods: This prospective observational study was carried out in Department of Surgery, Gandhi Medical College Bhopal and Associated Hamidia Hospital, Bhopal between July 2015 to October 2016. Results: Amoebic abscess (74%) is more common than pyogenic abscess (26%). Amoebic abscess is common in the age group of 31-50 years (73%), pyogenic in the age group of 51-70 years (73.1%). Male preponderance is found in case of amoebic liver abscess (90.5%). Right lobe involvement in common. Right upper quadrant pain, tenderness and fever are the most common clinical features. Alcoholism is most common risk factor (71.6%) and diabetes mellitus has strong association with pyogenic liver abscess (15.4%). E coli (19.2%) and klebsiella (11.5%) are the most common organisms cultured. Medical therapy is more useful in case of amoebic liver abscess (58.1%) while catheter drainage is more useful in case of pyogenic liver abscess (61.5%). Pleuropulmonary complications are much more common and complications rate is more common among pyogenic group. Conclusions: In our study, alcohol was found to be the most common predisposing factor for liver abscesses (68%), this underpin the finding of other studies. Amoebic liver abscess is a medically treated common infection prevailing in unhygienic condition, affecting people mostly between 30-40 years of age whereas pyogenic liver abscess patient commonly falls between 50-70 years age group. Both liver abscesses show a male preponderance. The present study also corroborates the catheter drainage procedure as a superior modality in treating pyogenic liver abscess.